The Development of An Initial Framework for Multi-Firm Industrial Safety Management Based On Cooperative Relationship: A Malaysia Case Study - Azizan, Ramli; Mazlin, Mokhtar; Badhrulhisham, Abdul Aziz (Elsevier Ltd, 2014)
The failure of the human system to prevent the occurrence of industrial accidents may lead to increment of cumulative occupational and disastrous accidents. Even some of the firms own safety management was thought to be of complacent. Hence an establishment of cohesive group which works cooperatively within an industrial estate might be appealing. Thus, the purpose of this paper is to provide an overview of an approach for cooperative safety management. This initiative might offer suggestions for further improvement in safety management to all industries in proximity regardless of their type and operational activities. The sources of information are academic articles, books, reports, direct interviews and internet web sites. The authors had highlighted a Malaysia case study on the initial framework developed for cooperative industrial safety management. This initial framework is addressed by five key factors, namely, institution, organization, legislation, financial, and technology, and it was then reviewed by a group of experts and practitioners in the field of industrial safety. Additionally, experts were also asked to share their opinions on the pro's and con's of this initiative. All of them basically had agreed with this concept; however they believe, this study is still in the initial stage and extensive work ought to be further explored. This is because Malaysia has its uniqueness in term of its multi-ethnic culture and thought, political status quo, administration constraints and readiness of industry to partake. However, amidst all challenges, the establishment of cooperative safety management in Malaysia is intriguing and noteworthy.